Environmental, Social and Governance (ESG) Integration in Financial Risk Management: Global Evidence From A Bibliometric and Systematic Literature Review - Andriyana Kurnianisa Meiratri; Aang Kunaifi (Journal of Social Research, 2025)
This study aims to analyze the integration of Environmental, Social, and Governance (ESG) factors into financial risk management through a systematic literature review and bibliometric analysis on a global scale. ESG has transitioned to a central focus in modern financial strategies due to its role in increasing a company's resilience to long-term risks and driving business sustainability. The study synthesizes findings from 492 Scopus-indexed documents during the period 2015–2024, using VOSviewer and Biblioshiny (R) for bibliometric mapping, trend identification, and thematic clustering. The results of the analysis show an exponential growth in scientific production (Annual Growth Rate 68.76%), indicating the acceleration of the maturity of this topic, supported by a strong collaborative network and wide geographical spread. The thematic analysis confirms that the main focus of the literature is centered on the relationship between ESG and financial performance and risk, as well as the crucial role of corporate governance in mitigating risk. Qualitatively, the literature identifies three main clusters: (1) the relationship between ESG and financial risk (systematic and idiosyncratic), (2) the incorporation of ESG data in sustainable investment decisions and policy frameworks, and (3) the influence of global governance and regulatory structures on risk mitigation. Overall, the study concludes that ESG integration significantly reduces financial risk and increases corporate resilience, while highlighting the need for more sophisticated quantitative methodologies to address data standardization and disclosure challenges.